Potensi Tumbuhan Melati Air (Echinodorus radicans) Terhadap Penurunan Kadar Timbal (Pb) dan Tembaga (Cu) Pada Limbah Cair Home Industry Batik di Desa Sendang Kabupaten Lamongan - Fatiha, Irssa Intan; Firdhausi, Nirmala Fitria; Zummah, Atiqoh (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the potential of water jasmine plants for optimal absorption time, reduction of heavy metal levels of Pb and Cu in Sendang batik liquid waste, and to observe plant morphology. This study uses an experimental method with a one-factor Completely Randomized Design (CRD) and four repetitions, resulting in 16 experimental plots. Heavy metal testing uses an Atomic Absorption Spectrophotometer (AAS). The results showed that (1) on days 9, 12, 15, and 18 of exposure, the decrease in Pb heavy metal levels was 3.71, 2.65, 0.80, and 0. 14 ppm, heavy metal Cu levels decreased consecutively by 4.09, 2.85, 0.31 and 0.26 ppm. (2) The average absorption rate of heavy metal Pb at exposure times of 9, 12, 15, and 18 consecutive days was 0.8, 0.14, 0.24 and 0.23 ppm, respectively, and the heavy metal Cu was 0.23, 0.28, 0.40 and 0. 33 ppm. (3) Morphological changes, namely the appearance of 2-3 new shoots for each treatment, the stems drooping slightly, the leaves changing color to yellow to brownish and brown spots throughout the treatment and on the 18th day one of the leaves died. (4) The initial results of the statistical test for Pb and Cu metals have a sig value of >0.05, where the data is normally distributed and homogeneous. (5) In the One Way Anova test results, sig = 0.000Ë‚0.05 or there is an effect of exposure time and the post hoc Pb test results are Ë‚0.05 while some Cu metals are Ëƒ0.05.